The Effect of Diary Writing on the Students’ Ability in Writing Recount Text at Grade X of SMA Negeri 4 Pematang Siantar - Maria Magdalena Situmorang; Bertaria Sohnata Hutauruk; Christian Neni Purba (Departement of Mathematics Education, 2023)
The purpose of this research was to investigate the effect of diary writing on writing abilities of 10th grade students at SMA Negeri 4 Pematang Siantar. Specifically, the focus was on their ability to write a recount text. The research employed a quantitative research method and adopted quasi-experimental design. This research enlisted a total of 353 students from 10th grade students of SMA Negeri 4 Pematang Siantar. From this population, 35 students from each class of X PMIA 2 and X PMIA 5 were chosen as sample. The assessment tools employed were pre-test and post-test in writing. The research utilized Brown's assessment standard for writing, which encompassed elements, iucluding content, structure, grammar, vocabulary, and technicalities. The process of analyzing data involved the use of SPSS version 21. This software facilitated the performance of several tests, including descriptive analysis, normality, Wilcoxon, homogeneity, and Mann Whitney tests. From the findings, it was revealed that Assymp. Sig. (2-tailed) was 0.017 < 0.05. Consequently, Ha was approved while Ho was declined. The skill of writing recount text among students at SMA Negeri 4 Pematang Siantar was found to be greatly impacted by the act of diary writing.